Geomythology in the Mëllerdall UNESCO Global Geopark (Grand Duchy of Luxembourg) and Adjacent Areas: Inventory and Assessment of Geotouristic Potential - Filipa Esteves; Charel Rollinger; Robert Weis; Birgit Kausch (Geoheritage, 2026)

Micronucleus assay in buccal and urothelial epithelial cells of wildland firefighters exposed to wildfire smoke - Filipa Esteves; Joana Madureira; Bela Barros; Sara Alves; Josiana Vaz; Marta Oliveira; Klara Slezakova; Adília Fernandes; Maria do Carmo Pereira; Simone Morais; Stefano Bonassi; João Paulo Teixeira; et al. (Journal of Hazardous Materials, 2025)

Impact of wildfire emissions exposure on the associations between levels of lung injury, lipid peroxidation, DNA oxidation, and exposure biomarkers - Bela Barros; Ana Margarida Paiva; Rui Azevedo; Sara Alves; Filipa Esteves; Adília Fernandes; Josiana Vaz; Maria José Alves; Klara Slezakova; João Paulo Teixeira; Solange Costa; Agostinho Almeida; et al. (Science of The Total Environment, 2025)

Impact of occupational exposure to wildfire events on systemic inflammatory biomarkers in Portuguese wildland firefighters - Filipa Esteves; Joana Madureira; Bela Barros; Sara Alves; Joana Pires; Sandra Martins; Marta Oliveira; Josiana Vaz; Klara Slezakova; Maria do Carmo Pereira; Adília Fernandes; Simone Morais; et al. (Environmental Research, 2025)

Occupational exposure to wildland firefighting and its effects on systemic DNA damage - Filipa Esteves; Joana Madureira; Carla Costa; Joana Pires; Bela Barros; Sara Alves; Josiana Vaz; Marta Oliveira; Klara Slezakova; Adília Fernandes; Maria do Carmo Pereira; Simone Morais; et al. (International Journal of Hygiene and Environmental Health, 2025)

Biomonitoring of firefighters' exposure to priority pollutant metal(loid)s during wildland fire combat missions: Impact on urinary levels and health risks - Ana Margarida Paiva; Bela Barros; Rui Azevedo; Marta Oliveira; Sara Alves; Filipa Esteves; Adília Fernandes; Josiana Vaz; Maria José Alves; Klara Slezakova; Maria do Carmo Pereira; João Paulo Teixeira; et al. (Science of The Total Environment, 2024)

Biomonitoring of polycyclic aromatic hydrocarbons exposure and short-time health effects in wildland firefighters during real-life fire events - Ana Margarida Paiva; Bela Barros; Marta Oliveira; Sara Alves; Filipa Esteves; Adília Fernandes; Josiana Vaz; Klára Slezáková; João Paulo Teixeira; Solange Costa; Simone Morais (Science of The Total Environment, 2024)

Measuring healthy ageing: current and future tools - Nádia Silva; Ana Teresa Rajado; Filipa Esteves; David Brito; Joana Apolónio; Vânia Palma Roberto; Alexandra Binnie; Inês Araújo; Clévio Nóbrega; José Bragança; Pedro Castelo-Branco; Raquel P. Andrade; et al. (Biogerontology, 2023)
Human ageing is a complex, multifactorial process characterised by physiological damage, increased risk of age-related diseases and inevitable functional deterioration. As the population of the world grows older, placing significant strain on social and healthcare resources, there is a growing need to identify reliable and easy-to-employ markers of healthy ageing for early detection of ageing trajectories and disease risk. Such markers would allow for the targeted implementation of strategies or treatments that can lessen suffering, disability, and dependence in old age. In this review, we summarise the healthy ageing scores reported in the literature, with a focus on the past 5 years, and compare and contrast the variables employed. The use of approaches to determine biological age, molecular biomarkers, ageing trajectories, and multi-omics ageing scores are reviewed. We conclude that the ideal healthy ageing score is multisystemic and able to encompass all of the potential alterations associated with ageing. It should also be longitudinal and able to accurately predict ageing complications at an early stage in order to maximize the chances of successful early intervention.

The Role of Beclin-1 Acetylation on Autophagic Flux in Alzheimer’s Disease - A. Raquel Esteves; Filipa Filipe; João D. Magalhães; Diana F. Silva; Sandra M. Cardoso (Molecular Neurobiology, 2019)

Occurrence of grapevine leafroll-associated virus 5 in Portugal: genetic variability and population structure in field-grown grapevines - Filipa Esteves; Margarida Teixeira Santos; José Eduardo Eiras-Dias; Filomena Fonseca (Archives of Virology, 2012)

Calpain-mediated MPP+ toxicity in mitochondrial DNA depleted cells - A. Filipa Domingues; A. Raquel F. Esteves; Russell H. Swerdlow; Catarina R. Oliveira; Sandra M. Cardoso (Neurotoxicity Research, 2008)